MODEL OF TEACHING MALAY LANGUAGE TO NON-NATIVE AND FOREIGN SPEAKER (Malaysian Journal of Learning and Instruction, 2024)
Purpose – This study aims to develop a teaching model of the Malay language for non-native and foreign speakers in schools. Implementing this model can assist educators in teaching the Malay language to students who do not use it as their first language in everyday use.Methodology – This study used a qualitative approach to develop teaching models for non-native and foreign Malay speakers. Interviews were conducted with 27 teachers and 23 stakeholders who are experts in teaching the Malay language, especially in teaching non-native speakers. A prototype model was developed thematically as a result of interviews using ATLAS.ti 22. Further, the prototype model was used by ten teachers from primary, secondary, and international schools in their teaching.Findings – This study has succeeded in developing a model for teaching the Malay language to non-native speakers and foreigners that includes five elements: teaching strategies, individual differences, input, social, and motivation. This model strongly emphasises instruction involving interaction, communication, and bilateral relations as a medium for students’ language acquisition and meaningful input. Verbal interaction between teachers and students can stimulate and improve students’ language skills in learning Malay.Significance – This model can help teachers teach the Malay language to non-native speakers and foreigners with a greater focus onachieving learning objectives. This model is expected to expand the usage, cultivate interest, and facilitate teaching the Malay language in educational institutions.